The importance of "like to like" ISI calibrations with freeze dried plasmas. European Concerted Action on Anticoagulation. Issue 4 (April 1998) - Poller, L; van den Besselaar, A M; Jespersen, J; Tripodi, A; Houghton, D
Abstract : AIM: To assess reliability of like to like and cross species calibrations using two types of certified freeze dried plasma calibrants--artificially depleted of vitamin K clotting factors, and from coumarin treated patients. METHODS: Six ECAA national control laboratories provided certified values for the freeze dried plasmas in terms of the human plain international reference preparation (IRP) (BCT/441) with the manual prothrombin time technique. Eight other ECAA national laboratories determined international sensitivity index (ISI) values in full fresh plasma same species and cross species WHO calibrations against a low ISI human IRP (BCT/441) of the ECAA low ISI human thromboplastin and high ISI ECAA rabbit thromboplastin. Parallel calibrations were performed using the certified values. RESULTS: Calibrations on fresh plasmas of the human ECAA reference thromboplastin (stated ISI = 0.95) gave ISI of 0.957 against the human IRP and 1.66 against the rabbit IRP. The ECAA rabbit (stated ISI = 1.67) gave an identical value on the fresh plasma calibration v the human IRP. With freeze dried depleted plasmas certified in terms of the human IRP, the ISI of the ECAA human was 1.01, but the ECAA rabbit (stated ISI = 1.67) gave a low ISI of 1.47. The freeze dried coumarin plasmas gave an ISI of 0.943 for the ECAA human but only 1.493 for the ECAA rabbit. CONCLUSIONS: Fresh plasmas give reliable ISI when calibrating thromboplastins in same species and cross species calibrations. Freeze dried plasmas certified in terms of a single IRP, whether artificially depleted or of coumarin plasma origin, cannot be used for calibration of dissimilar thromboplastins.